Peran Pesantren dalam Penanaman Moderasi Beragama: Tinjauan Pustaka Sistematis - Syahrin, Alif Alfi; Noviani, Fitri; Mustika, Bunga (Universitas Al Azhar Indonesia, 2024)
The diversity of religious communities creates challenges in maintaining harmony between religious communities. Various acts of intolerance to radicalism are problems that can disrupt harmony and damage the consensus of the Indonesian nation. Islamic boarding schools as Islamic religious educational institutions have a role in teaching and disseminating understanding that can strengthen and maintain harmony between religious communities in Indonesia, one of which is religious moderation which can be implemented in various ways and approaches for students. The purpose of this study is to identify various types of religious moderation instillation for students. This study uses a systematic literature review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A systematic search was conducted on the Scopus database using the Publish Or Perish application based on publications from 2019 to 2024 using predetermined keywords. The determination of selection criteria resulted in 8 scientific articles to be analyzed in this study. The results of the study show that the instillation of religious moderation can be carried out by Islamic boarding schools in various ways, such as by combining modern education with traditional Islamic boarding school traditions, implementing multicultural education based on local culture, through understanding Sufi orders, utilizing digital learning, implementing hidden curriculum, organizing interfaith and cultural dialogues and halaqah, using the taghyir approach and strengthening intellectual traditions in the Islamic boarding school environment.Keyword - Religious Moderation, Pesantren, Santri, Systematic Literature Review.